Postoperative onset lateral hinge fracture is a risk factor for delayed union of the tibial tuberosity in medial opening wedge distal tibial tuberosity osteotomy - Hiroyasu Ogawa; Yutaka Nakamura; Masaya Sengoku; Tetsuya Shimokawa; Kazuichiro Ohnishi; Haruhiko Akiyama (Elsevier, 2024)
Background: This study aimed to evaluate bone union of the tibial tuberosity in patients undergoing medial opening wedge distal tibial tuberosity osteotomy (OWDTO). It was hypothesized that bone union of the tibial tuberosity could be associated with lateral hinge fractures (LHFs), but not thickness of the tibial tuberosity osteotomy. Methods: Data of 61 consecutive patients who underwent OWDTO were retrospectively reviewed. Radiographic parameters of the lower limb and LHFs were evaluated. Thickness of the tibial tuberosity osteotomy and bone union of the tibial tuberosity were assessed at 1, 2, 3, 4, and 5 cm distal to the most proximal part of the tibial tuberosity on computed tomography. Bone union was assessed. Factors related to bone union of the tibial tuberosity were analyzed. Results: There were 13 postoperative onset LHFs: all healed with conservative treatments within 6 months after surgery. The total score of bone union of the tibial tuberosity was 8.4 ± 2.1 points, which correlated with age, postoperative medial proximal tibial angle (MPTA), correction angle, and postoperative onset LHF (r = 0.307, 0.388, 0.275, and −0.624, respectively; p = 0.016, 0.002, 0.033, and <0.001, respectively). Regression coefficient for postoperative onset LHF, postoperative MPTA, and body mass index were −0.619 (p < 0.001), 0.285 (p = 0.003), and −0.227 (p = 0.021), respectively. Conclusion: Postoperative onset LHFs, but not thickness of the tibial tuberosity osteotomy, were a risk factor for delayed union of the tibial tuberosity following OWDTO. Furthermore, to prevent delayed union of the tibial tuberosity, postoperative onset LHFs should be prevented. Level of evidence: LEVEL III, Case-control study.